The Perception of Undergraduate Students in Jakarta on the Consumption of Cultured Meat - Virginia, Jeslin Audrey; Widjojo, Clara Ayu; Inaray, Ivetta Izhora; Ratnasari, Nanda Rizqia Pradana (Indonesian Journal of Life Sciences, 2021)
Cultured meat, which is meat produced by cell culture, is forecasted to be a prominent solution for the growing meat demand. While startups have been established and cultured meat has been marketed in other countries, research about consumer perception is still lacking in Indonesia. The objective of this study is to identify and analyze the customer standpoint, specifically among undergraduate students in Jakarta, regarding cultured meat production and consumption through an online survey. It is hypothesized that there is an effect of being an i3L, and, a biology or food-related major undergraduate student to the cultured meat consumption acceptance. Moreover, it is predicted that there will be a positive change in cultured meat consumption acceptance after watching an educational video included in the survey. Especially, from the group of vegetarians who are motivated to support animal welfare (i.e. No killing of animals) and improve environmental conditions (i.e. Reduce carbon emission). The results showed that study majors and vegetarian status was not significantly correlated with cultured meat acceptance. Nonetheless, previous knowledge about cultured meat positively affects the acceptance. Moreover, the educational video was able to increase the participants’ acceptance. This implies that awareness raising activities, such as advertisements and campaigns, would be effective.